Ekspresi Estetik Bangsa Indonesia dalam Tutur Pantun - Andayani, Ruli (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Pantun is one of the Indonesian speech culture that contains noble thoughts. In the speech tradition, pantun is used as a recreative and educational tool. Pantun has aesthetic values, elements of art, beauty that reflect the expression of the Indonesia people in looking at life. This research aims to analyze the aesthetic value of pantun. The research method used is descriptive-qualitative. The research data is in the form of words in the pantun array. Data collection techniques through literature study. The data analysis is done by (1) identifying elements that contribute to building the aesthetic concept; (2) identifying elements that get emphasis; and (3) concluding the harmony between aesthetic elements in forming a unity of meaning. The results of the data analysis state that pantun holds cultural aesthetics, especially evident in the use of rhyme and philosophy. The results of the data analysis state that pantun has aesthetics, which can be seen in the cover, rhyme, and harmony. Sampiran images of nature as an introduction to the philosophical thoughts contained in the body. The aesthetics of pantun are closely related to ethical elements so that beauty appears in the form as well as the holiness and nobility of the ethics it contains.